INTERACTIVE METHODS OF COMPUTER SCIENCE USED IN FOREIGN COUNTRIES, NEW METHODS AND TOOLS OF TEACHING WERE DISCUSSED (Web of Teachers: Inderscience Research, 2024)
Interactive methods of computer science used in foreign countries, new methods and tools of teaching were discussed.